The type III secretion system effector SeoC of Salmonella enterica subspecies salamae and arizonae ADP-ribosylates Src and inhibits opsono-phagocytosis - Pollard,DJ; Young,JC; Covarelli,V; Herrera-León,S; Connor,TR; Fookes,M; Walker,D; Echeita,A; Thomson,NR; Berger,CN; Frankel,G (Infection and Immunity, 2016)
Salmonella spp. utilize type III secretion systems (T3SS) to translocate effectors into the cytosol of mammalian host cells, subverting cell signaling and facilitating the onset of gastroenteritis. In this study we compared a draft genome assembly of S. enterica subsp. salamae strain 3588/07 (S. salamae) against the genomes of S. enterica subsp. enterica serovar Typhimurium strain LT2 and S. bongori strain 12419. S. salamae encode the Salmonella pathogenicity island (SPI)-1; SPI-2 and the locus of enterocyte effacement (LEE) T3SSs. Though several key S. Typhimurium effector genes are missing (e.g. avrA, sopB and sseL), S. salamae invades HeLa cells and contain homologues of S. bongori sboK and sboC, which we named seoC. SboC and SeoC are homologues of EspJ from enteropathogenic and enterohaemorrhagic E. coli (EPEC and EHEC), which inhibits Src kinase-dependent phagocytosis by ADP-ribosylation. By screening 73 clinical and environmental Salmonella isolates we identified EspJ homologues in S. bongori, S. salamae and S. enterica subsp. arizonae (S. arizonae). The β-lactamase TEM-1 reporter system showed that SeoC is translocated by the SPI-1 T3SS. All the Salmonella SeoC/SboC homologues ADP-ribosylate Src E310 in vitro. Ectopic expression of SeoC/SboC inhibited phagocytosis of IgG-opsonized bead into Cos-7 cells stably expressing GFP-FcγRIIa. Concurrently, S. salamae infection of J774.A1 macrophages inhibited phagocytosis of beads, in a seoC dependent manner. These results show that S. bongori, S. salamae and S. arizonae share features of the infection strategy of extracellular pathogens EPEC and EHEC and sheds light on the complexities of the T3SS effector repertoires of Enterobacteriaceae.